Issues Dedicated to Nature in the Encyclical Letter Laudato Si’ of the Holy Father Francis - Żarska, Barbara (Studia Ecologiae et Bioethicae, 2017)
The Laudato Si’ encyclical of the Holy Father Francis is a recent document addressing the issue of the global environmental crisis and as well as the man – environment relationship. The present paper provides an analysis of the Encyclical’s content with respect to the manners of recognizing the crisis, arguments for nature protection, and proposed activities aimed at overcoming the environmental crisis. The theses contained in the Encyclical are consistent with strategic documents, programs, and laws at the national level, the European Union, and the international level. The Holy Father, however, gave a slightly different direction to activities undertaken in the area of nature conservation and improvement of the man – environment relationship. Pope Francis pointed to the deep dependence between the ecological crisis and the social crisis. He pointed to the socio-ecological nature of this crisis. The Laudato Si’ encyclical is a document of worldwide importance in the fight against the socio-ecological crisis.